Alkaline induced-cation crosslinking biopolymer soil treatment and field implementation for slope surface protection - Lee, Minhyeong; Chang, Ilhan; Kang, Seok Jun; Lee, Dong Hyuk; Cho, Gye Chun (Geomechanics and Engineering, 2023)
Xanthan gum and starch compound biopolymer (XS), an environmentally friendly soil-binding material produced from natural resources, has been suggested as a slope protection material to enhance soil strength and erosion resistance. Insufficient wet strength and the consequent durability concerns remain, despite XS biopolymer-soil treatment showing high strength and erosion resistance in the dried state, even with a small dosage of soil mass. These concerns need to be solved to improve the field applicability and post-stability of this treatment. This study explored the utilization of an alkaline-based cation crosslinking method using calcium hydroxide and sodium hydroxide to induce non-thermal gelation, resulting in the enhancement of the wet strength and durability of biopolymer-treated soil. Laboratory experiments were conducted to assess the unconfined compressive strength and cyclic wetting-drying durability performance of the treated soil using a selected recipe based on a preliminary gel formation test. The results demonstrated that the uniformity of the gel structure and gelling time varied depending on the ratio of crosslinkers to biopolymer; consequently, the strength of the soil was affected. Subsequently, site soil treated with the recipe, which showed the best performance in indoor assessment, was implemented on the field slope at the bridge abutment via compaction and pressurized spraying methods to assess feasibility in field implementation. Moreover, the variation in surface soil hardness was monitored periodically for one year. Both slopes implemented by the two construction methods showed sufficient stability against detachment and scouring, with a higher soil hardness index than the natural slope for a year.
Keywords: Alkalines; Erosion resistance; Field application; Field implementation; Hardness biopolymer; Slope surfaces; Sodium hydroxides; Soil treatments; Treated soils; Wet strength; calcium hydroxide; crosslinking; field application; hardness biopolymer; slope protection; sodium hydroxide; soil